Hispathology of the gill, abdomen, and lymphoidorgan of giant black tiger shrimp (Panaeus monodon) infected with white spot syndrome virus (WSSV). - Apines, John Sepacio (2004.)
Histological changes in giant black tiger shrimp, penaeus monodon, were investigated at various time intervals after injection with white spot syndrome virus (WSSV). After infection with the virus, mortalities were odserved. Gills, abdomen and lymphoid organ (LO) were then dissected and subjected to histological examination. The study revealed that the lymphoid organ was the most severely damaged compared to the gills and abdomen. The abdomen, although low in prevalence, was one of the target organs of the virus. Light microscopy showed the aggregation of hemocytes in the abdominal muscles of the shrimp. The infected shrimp were found to had a high prevalence of apoptotic cells. The results of this study supported the earlier findings that cell death in viral infection may have resulted mainly from apoptosis and that increasing numbers of apoptotic cells probably caused the death in WSSV-infected shrimp. Moribund shrimp had extensive deterioration of vital tissues such as the gills and lyphoid organs, thus, affecting vital processes in the shrimp body. Gross signs of lethargy and weakness were observed in the moribund shrimps. Hemocytes aggregation as well as formation of spheroids were observed in the hemal sinuses of the LO, the abdominal region and the gills. The results are discussed in relation to the hypotheses of acquired tolerance and quasi-immune response in shrimp.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Shrimp (black tiger); Penaeus monodon; White spot syndrome (WSSV)